Knowledge and Behavior of the Tembung Village Community about Sunscreen to Prevent Melanoma - M. Fakhri Ali; Pimpin Utama Pohan; Bambang Prayugo; Heru Rahmadhany (Sumatera Medical Journal, 2023)
Background: Indonesia is one of the tropical countries in the world that is illuminated by the sun all year round. High sun exposure requires Indonesian people to be more concerned about skin protection, especially melanoma. The risk factor for melanoma is exposure to UV radiation so melanoma can be prevented by reducing exposure to UV rays, one of them by using sunscreen. The use of sunscreen with SPF 15+ every day can reduce the risk of developing melanoma by 50%. Objective: This study aims to obtain information about the level of knowledge and behavior of people in Tembung about the use of sunscreen to prevent melanoma. Methods: The research design used is descriptive research using a cross-sectional study. The Data was obtained through the distribution of online questionnaires with 100 people. Furthermore, the data obtained will be processed using SPSS. Results: 41 people had sufficient knowledge about melanoma, 67 people had less knowledge about sunscreen, and 38 people had good behavior. Conclusion: Most of people in Tembung have sufficient knowledge about melanoma, lack knowledge about sunscreen, and have a good behavior in using sunscreen.